Dedicated Boundary Element Modeling for Nanoparticle‐on‐Mirror Structures Incorporating Nonlocal Hydrodynamic Effects. Issue 12 (3rd October 2022) - Zheng, Xuezhi
Abstract: A boundary element modeling for predicting the plasmonic response from a Nanoparticle‐on‐Mirror (NPoM) structure is proposed. The NPoM can be considered as one of the most important platforms in the research on nanophotonics. Instead of using the local response model to describe the optical response of metals, the nonlocal hydrodynamic model is used to account for the dynamics of free electrons in the metallic NP and the metallic mirror beneath. A system of boundary integral equations (BIEs) is derived to describe the interaction of light with the NPoM structure. The BIEs are solved by the boundary element method. To validate the implementation, two exemplary structures are considered: the Nanosphere‐on‐Mirror structure and the Nanocube‐on‐Mirror structure. By contrasting with the results from previous works and the results from a generalized T‐matrix method, both a qualitative and quantitative agreement in the near field and the far field regimes are observed. Abstract : This work proposes a dedicated boundary element modeling for the nanoparticle‐on‐mirror (NP) structure. Lying at the core of the modeling scheme are boundary integral equations (BIEs). The BIEs are constructed by using the surface equivalence principle and the Green functions. The BIEs are numerically solved by the boundary element method (BEM). The BEM implementation is applied to two exemplary NPoM structures and good agreements are demonstrated.